NPHS2 gene mutation, atopy, and gender as risk factors for steroid-resistant nephrotic syndrome in Indonesians - Dedi Rachmadi; Danny Hilmanto; Ponpon Ijradinata; Abdurahman Sukadi (Paediatrica Indonesiana, 2011)
Background Steroid-resistant nephrotic syndrome (SRNS) often develops into end stage renal disease. Previous studies have reported that NPHS2 gene mutation, gender, and atopic history are risk factors associated with SRNS. Interethnic, sociocultural, and environmental differences have also been suggested to affect these mutations.Objective To analyze possible risk factors for SRNS, including NPHS2 gene mutations (412C→T and 419delG), gender and atopic history, in Indonesian subjects with SRNS.Methods A case-control study with 153 subjects, consisting of 88 SRNS patients and 65 control subjects, was undertaken in 10 Indonesian teaching centre hospitals from September 2006 to December 2007. Analysis of the NPHS2 gene mutation in 412 C→T was performed by amplification refractory mutation system-polymerase chain reaction (ARMS-PCR), while that for the NPHS2 gene mutation in 419delG was performed by restriction fragment length polymorphism (RFLP). Data was analyzed by multiple logistic regression.Results In our Indonesian subjects, the significant risk factors for SRNS were male gender (OR=2.21; CI 95%:1.07-4.56, P=0.036), NPHS2 412C→T gene mutation (OR=18.07; CI 95%:6.76-48.31, P<0.001), and NPHS2 419delG gene mutation (OR=4.55; CI 95%:1.66-12.47, P=0.003). However, atopic history was not a significant risk factor for SRNS (OR=1.807; CI 95%:0.642-5.086, P=0.262).Conclusion NPHS2 412C→T and 419delG gene mutations, as well as male gender are risk factors for SRNS in Indonesian subjects. Atopic history was not significantly associated with SRNS in our subjects. [Paediatr Indones. 2011;51:272-6].